Determination of minority carrier diffusion length of sprayed-Cu2ZnSnS4 thin films. (April 2016) - Courel, Maykel; Valencia-Resendiz, E.; Pulgarín-Agudelo, F.A.; Vigil-Galán, O.
Highlights: Ln values of spray-deposited CZTS thin films are studied. Ln values as a function of CZTS compositional ratios are reported. Higher Ln values are reached for optimal CZTS compositional ratios. Non-optimal compositional ratios showed relatively low Ln values. Ln values in the range of 0.11–0.17 μm are obtained. Abstract: Despite Cu2 ZnSnS4 (CZTS) is a potential candidate for solar cell applications, so far, low efficiency values have been reported. In particular, for spray-deposited CZTS, efficiencies lower than 2% are commonly achieved. It is well known that one of the most important parameters governing solar cell performance is minority carrier diffusion length ( Ln ). In this work, CZTS thin film solar cells with different compositional ratios are fabricated in order to study its impact on Ln values. The Ln parameter is calculated for sprayed-CZTS layers using external quantum efficiency measurements in conjunction with optical absorption coefficient versus wavelength measurements – for the first time. Values in the range of 0.11–0.17 μm are obtained emphasizing the need for improving sprayed-CZTS crystalline quality.